Ghosts of Guinea Worms: A Rare Case of Extensive Calcified Guinea Worms - Davra, Sanket Vinubhai; Pushkar, Kumar (Journal of Neonatal Surgery, 2025)
Dracunculiasis, or Guinea worm disease, is a parasitic infection caused by Dracunculus medinensis. Although eradicated in India since 2000, residual calcified worms can persist asymptomatically in affected individuals. We present a rare case of a 45-year-old male washerman from Rajasthan, India, with extensive calcified guinea worms detected incidentally during radiographic evaluation for leg pain. This case underscores the importance of recognizing characteristic radiographic features of calcified D. medinensis and highlights the enduring legacy of a once-prevalent disease.